2004
DOI: 10.1590/s0073-47212004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal characterization of Pseudonannolene strinatii (Spirostreptida, Pseudonannolenidae)

Abstract: ABSTRACT. The chromosomes of the cave millipede Pseudonannolene strinatii Mauriès, 1974 were investigated. The diploid chromosome number was found to be 2n=16, XX/XY; the C-banding technique revealed a large amount of heterochromatin while the silver staining technique (Ag-NOR) evidenced the presence of heteromorphism of the NORs in some cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
4
4
0
Order By: Relevance
“…The large amount of constitutive heterochromatin found in Pseudonannolene tocaiensis and P. silvestris, especially the amount found in the first two pairs of autosomes, corroborates with the results found in another species of this genus, P. strinatti (Campos & Fontanetti 2004). Campos & Fontanetti (2004) observed that in Pseudonannolene strinatti approximately 55% of the male genome consisted of heterochromatin, with this value being close to 57% in the females.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The large amount of constitutive heterochromatin found in Pseudonannolene tocaiensis and P. silvestris, especially the amount found in the first two pairs of autosomes, corroborates with the results found in another species of this genus, P. strinatti (Campos & Fontanetti 2004). Campos & Fontanetti (2004) observed that in Pseudonannolene strinatti approximately 55% of the male genome consisted of heterochromatin, with this value being close to 57% in the females.…”
Section: Discussionsupporting
confidence: 86%
“…Campos & Fontanetti (2004) observed that in Pseudonannolene strinatti approximately 55% of the male genome consisted of heterochromatin, with this value being close to 57% in the females. These results are similar to those found in other species of diplopods, in which the C-banding has evidenced the presence of large heterochromatic blocks.…”
Section: Discussionmentioning
confidence: 85%
“…Sumner (1990), however, affirms that chromosomic variants, such as variations in the heterocromatin, are kept in populations as a heteromorphism, not necessarily causing reduction of fertility and in this way not becoming reproductive barriers, and thus not leading to speciation. As expected, the nucleolus organizer regions are observed in pair 4 in all populations and correspond to heterochromatic portions (Campos & Fontanetti, 2004), as described by various authors for different groups animals, including others diplopods (Souza et al, 2005;Godoy et al, 2008). The silver impregnation revealed heteromorphisms for the size of the NOR in the chromosomes of the individuals of Jeremias and Areias de Cima Cave.…”
Section: Discussionsupporting
confidence: 84%
“…These present high amounts of the constitutive heterochromatin, about 65% of the diploid genoma of the species, a fact already observed in this and other species of other orders (Vitturi et al, 1997;Fontanetti et al 2002;Campos & Fontanetti, 2004;2005;Souza et al, 2005;Godoy et al, 2008). Pairs 5 and 6 of the individuals of the Laboratório Cave and pairs 4 and 5 of Jeremias Cave are heteromorphic based on C-banding.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation